PENGGUNAAN MEDIA POWER POINT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII.6 PADA PEMBELAJARAN KETERAMPILAN DI SMPN 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - ARIEF FARIATNO, Dra. Zubaidah, M. Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
This study aims to knowing whether the use of Power Point media canincrease motivation and student learning outcomes class VII.6 onlearning skill in SMPN 1 V Koto Kampung Dalam, the district ofPadang Pariaman. This type of research is classroom action researchwith research subjects at class VII.6 in SMPN 1 V Koto KampungDalam. The result showed that use Power Point media can increasemotivation and students learning outcomes with average motivation ofcycle I 3.198 and average of cycle II 3.41 as well as the averagelearning outcomes of cycle I 73.10 and average of cycle II 89.31.Kata Kunci: Media Power Point, Motivasi, Hasil Belajar